Purification of Beryllium by Acetylacetone-EDTA Solvent Extraction - Moore, R. E.; Shaffer, J. H.; Baes, C. F. jr.; McDuffie, H. F.; Bamberger, C. E. L. (Academic Press Inc., 1963)
Fil: Bamberger, C. E. L. Comisión Nacional de Energía Atómica; Argentina